UPAYA MENGATASI KESULITAN BELAJAR SISWA PADA MATERI PERSAMAAN GARIS LURUS DENGAN PENDEKATAN SAINTIFIK DI SMP - Tifa Hensifa Hanum (Universitas Sultan Ageng Tirtayasa, 2020)
The research is carried out in 3 cycles, each cycle consists of the stages of planning, action, observation, reflection. While the learning approach in this study uses a saintific approach through the student activity sheet (LKS) in a structured way so that students can build their own knowledge by completing the LKS in groups. The data in this study was obtained by the score of tests, observations and questionnaire. The success criteria of this action is that the student is declared successful if: (1) The test result is more than 67.55; (2) The affective score of the observation of the learning process is more than 13; (3) Questionnaire scores for students' responses in more than 26. The study was declared successful in the event of a student who was declared successful in learning from cycle I to the III cycle. From the results of the research obtained, the students gained a score of more than 67.55 on the I cycle of 40%, cycle II of 67.5% and cycle III by 85%. From the observation gained an idea of increasing students' activity in the study in cycle I of 42.5%, cycle II by 65% and cycle III by 85%. The results of the questionnaire of students' responses to the study gained an overview on cycle I of 47.5%, cycle II of 72.5% and cycle III by 87.5%. In the learning of equations the results always increase in other words students who have difficulty learning less, while from the observation results gained increased activity, students are actively involved in the learning process. As for the results of the questionnaire that learning with a costructivical approach enhances students ' responses in learning, and promotes students to learn to construct their own learning materials and when experiencing difficulties Students are assisted by a group of friends who first understand the material learned and if in a group there is no bias to resolve the difficulties faced directly asking the teacher. Keywords: Student’s obstacle, Saintific Approach.